Hemangiopericytomas: Spatial Intracranial Location in a Voxel‐Based Mapping Study. Issue 3 (1st April 2020) - Li, Lianwang; Song, Ming; Zhang, Chuanbao; Qian, Zenghui; Li, Yiming; Li, Runting; Li, Chao; Yang, Zhengyi; Zhou, Dabiao
ABSTRACT: BACKGROUND AND PURPOSE: To investigate the preferred location of intracranial hemangiopericytomas (IHPCs) with voxel‐based mapping and 3‐dimensional reconstruction from MRI data. METHODS: Gadolinium‐enhanced tumors of 258 primary and single IHPCs were segmented semi‐automatically, followed by manual checking and editing of boundaries. The lesions were registered to Montreal Neurological Institute standard anatomical space, and heat‐map and 3‐dimensional rendered frequency images were generated. All tumors were then superimposed on the Anatomical Automatic Labeling (AAL) template to further investigate the difference in the tumor location based on the voxel‐wise frequency of occurrence with respect to laterality, sex, age, and pathologic grade. RESULTS: The 3‐dimensional rendered images show that the tumors commonly located in the posterior cranial cavity, surrounding the tentorium. The posterior third of the superior sagittal sinus and the confluence of sinuses were commonly affected. According to the analysis of tumor occurrence frequency in the AAL template, IHPCs were mainly observed in the limbic lobe, occipital lobe, and cerebellum. Tumors in younger patients preferentially located in the right occipital region ( P = .027), whereas those with higher pathological grade more often located in the left parietal lobe ( P = .034). CONCLUSIONS: This is the first voxel‐based study to explore the predilection site of IHPCs. Our study suggests that these tumors commonly affect the posterior cranial cavity, adjoining the tentorium and venous sinus. Further research is needed to investigate the possible factors underlying these topographic preferences.